THE CONTRIBUTION OF ARM LENGTH AND ARM MUSCLE STRENGTH TO THE DISCUS THROW ABILITY OF PUTERA STUDENTS OF SMA NEGERI 1 PINRANG - Agus Sutriawan; Muhammad Akbar Syafruddin; Sufitriono Sufitriono (Hanoman Journal: Physical Education and Sport, 2022)
This study aims to determine; (1) Is there a contribution between the length of the arm on the discus throwing of male students at SMA Negeri 1 Pinrang. (2) Is there a contribution between arm muscle strength on the discus throw of male students at SMA Negeri 1 Pinrang. (3) Is there a contribution between arm length and arm muscle strength for male students at SMA Negeri 1 Pinrang. The method used in this research is a quantitative descriptive method. The population in this study were all students at SMA Negeri 1 Pinrang, totaling 109 students. The sample in this study amounted to 32 students. The sampling technique used simple random sampling (randomly). Based on the results of data analysis and hypothesis testing, it can be concluded as follows: (1) There is a significant contribution between arm length and discus throwing for male students of SMA Negeri 1 Pinrang, the contribution is 23.7% with an R value of 0.487 (Pvalue = 0.005α 0, 05). (2) There is a significant contribution between arm muscle strength and discus throwing for male students at SMA Negeri 1 Pinrang, the contribution is 26.0% with an R value of 0.510 (Pvalue = 0.003 α 0.05). (3) There is a significant contribution between arm length and arm muscle strength for male students at SMA Negeri 1 Pinrang with a contribution of 51.7% with an R value of 0.719 (Pvalue = 0.000 α 0.05); and Fcount value of 15.494